2023
DOI: 10.1038/s41419-023-05915-9
|View full text |Cite
|
Sign up to set email alerts
|

USP11-mediated LSH deubiquitination inhibits ferroptosis in colorectal cancer through epigenetic activation of CYP24A1

Abstract: Ferroptosis is an iron-dependent form of regulated cell death characterized by lipid peroxidation. Colorectal cancer (CRC) cells evade ferroptosis despite their requirement of substantial iron and reactive oxygen species (ROS) to sustain active metabolism and extensive proliferation. However, the underlying mechanism is unclear. Herein, we report the role of lymphoid-specific helicase (LSH), a chromatin-remodeling protein, in suppressing erastin-induced ferroptosis in CRC cells. We demonstrate that erastin tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Moreover, p53 also functions in ferroptosis and lysosome-dependent cell death. It is noteworthy that members of the deubiquitinase family, such as USP8/11/18/48 and OTUD1/4, along with the heat shock protein family (HSP70/90/A8), exert precise regulatory effects on multiple RCD subroutines 313 , 314 , 457 , 458 , 459 , 460 .…”
Section: The Crosstalk Between Non-apoptotic Rcd Subroutines and Thei...mentioning
confidence: 99%
“…Moreover, p53 also functions in ferroptosis and lysosome-dependent cell death. It is noteworthy that members of the deubiquitinase family, such as USP8/11/18/48 and OTUD1/4, along with the heat shock protein family (HSP70/90/A8), exert precise regulatory effects on multiple RCD subroutines 313 , 314 , 457 , 458 , 459 , 460 .…”
Section: The Crosstalk Between Non-apoptotic Rcd Subroutines and Thei...mentioning
confidence: 99%
“…This destabilization is facilitated by the cullin-RING E3 ubiquitin ligase complex Cullin-RING ligase 4 (CRL4)-DDB1 and CUL4 associated factor 8 (DCAF8), which mediates polyubiquitination and subsequent proteasomal degradation of HELLS in cancer cells [ 158 ]. Furthermore, the deubiquitinating enzymes ubiquitin specific peptidase 5 (USP5) and USP11 inhibit ferroptosis by mediating the deubiquitination and stabilization of HELLS in hepatocellular carcinoma and colorectal cancer, respectively [ 159 , 160 ].…”
Section: Protein Degradation In Ferroptosismentioning
confidence: 99%
“…It has been reported that USP11 promotes autophagy activation and induces ferroptosis by deubiquitinating and stabilizing Beclin 1, thereby regulating spinal cord ischemia-reperfusion injury ( Rong et al, 2022 ). In addition, Duan et al found that USP11 can mediate LSH deubiquitination and activate CYP24A1 to inhibit ferroptosis in colorectal cancer ( Duan et al, 2023 ). Zhu et al found that Sirt3 decreased and ferroptosis occurred after the development of IVDD.…”
Section: Progress In Research On Ferroptosis In Ivddmentioning
confidence: 99%